Understanding market preferences for nutritious foods in urban Ethiopia – A discrete choice experiment approach - Wanyama, Rosina; Onyango, Kevin; Teferi, Ermias; Jordan, Irmgard; Lundy, Mark; Chege, Christine G K (2024)
-Current food systems are unable to support sustainable healthy diets: 2.8 Billion people globally cannot afford a healthy diet (SOFI, 2024). -Poor diets are primary contributors of all forms of malnutrition, and leading cause of diseases worldwide: Globalization, population growth, technology development, food marketing, urbanization, climate change and variability etc. -Markets and food environment shape the interface between food production and consumption.